The hybrid polyhydroxyurethane materials synthesized by a prepolymerization method from CO2-sourced monomer and epoxy. (December 2016) - Ke, Jiexi; Li, Xiaoyun; Wang, Feng; Kang, Maoqing; Feng, Yuelan; Zhao, Yuhua; Wang, Junwei
Graphical abstract: We successfully synthesized hybrid PHU materials from CO2, PPGDGE, amines, and BADGE through three steps process. The CO2 -sourced monomer was synthesized by the coupling reaction of CO2 with PPGDGE. The −NH2 pre-polymers were obtained by the ring-opening of CO2 -sourced monomer with amine, and pre-polymers reacted with corresponding content BADGE to produce hybrid PHUs through compression molding. Highlights: CO2 -sourced monomer was synthesized by a cycloaddition reaction from CO2 and polypropylene glycol diglycidyl ether. The selectivity of formed cyclocarbonate was acquired through mathematical simulation calculation method from the results of 1 H NMR. −NH2 terminated pre-polymers were synthesized. The hybrid PHU materials were synthesized from the reaction of pre-polymer and BADGE. The effect of amine ratio, type and BADGE content on the properties of PHUs was studied. Abstract: A series of hybrid polyhydroxyurethane (PHU) materials were prepared from CO2, polypropylene glycol diglycidyl ether, amines, and bisphenol-A diglycidyl ether (BADGE). Firstly, the five-membered cyclocarbonate (5CC) as the CO2 -sourced monomer was synthesized by a cycloaddition reaction from CO2 and polypropylene glycol diglycidyl ether at 120 °C under 10 bar CO2 pressure in the presence of an amberlyst catalyst. The selectivity of 5CC was confirmed through an analog computation method based on the results of 1 H NMR. Then, 5CC was reacted with excessive amines to produce the −NH2 terminated pre-polymers. Finally, the pre-polymers reacted with BADGE to produce hybrid PHU materials. The effect of amine type and BADGE content on the properties of PHUs was studied by means of Fourier transform infrared spectra, dynamic mechanical thermal analysis, and thermogravimetric analysis and solvent swelling test. The results indicated that introducing BADGE as a chain extender not only enhances the gelation rate of PHU, but also improve the mechanical and thermal properties of PHU materials.